2017
DOI: 10.26418/jpmipa.v8i2.21174
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pembelajaran Kooperatif Tipe TGT Dan Gaya Belajar Model Vark Terhadap Hasil Belajar Kimia Sekolah Pada Mahasiswa Program Studi Pendidikan Kimia

Abstract: This research aims to investigate the effects of Teams Games

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Working in groups in the laboratory teaches students to work cooperatively. In line with Kurniati et al (2017), the cooperative learning model provides students with opportunities to interact openly and pleasantly to create positive interdependence and develop relationships between groups.…”
Section: Resultsmentioning
confidence: 99%
“…Working in groups in the laboratory teaches students to work cooperatively. In line with Kurniati et al (2017), the cooperative learning model provides students with opportunities to interact openly and pleasantly to create positive interdependence and develop relationships between groups.…”
Section: Resultsmentioning
confidence: 99%
“…Previous relevant research was carried out by Amiliya et al (2019) with the title "Matematical problemsolving ability through learning methods whole brain teaching (wbt) in terms of David Kolb's learning style on quadrilateral material". The results of the study show that the problemsolving ability of students in terms of David Kolb's (Kurniati & Kurniawan, 2017) learning style (experimental class) is better than the learning method (control class) so it can be concluded that each different learning style has different problem-solving abilities (Amiliya et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…Gender is a concept that is the result of human thinking created by a fluctuating society that can differ due to differences in religion, race, and customs (Arief, Sihkabuden & Ulfa, 2018). By knowing the characteristics of students' learning styles, learning objectives will be achieved (Kurniati & Kurniawan, 2017).…”
Section: Introductionmentioning
confidence: 99%